Knowledge, attitudes, and practices regarding China’s DRG payment policy among healthcare professionals in tertiary and secondary hospitals in Yunnan Province: a cross-sectional study - Yang, Jian; Qin, Dan; Li, Fan (Frontiers in Public Health, 2025)
BackgroundThe China Healthcare Security Diagnosis Related Groups (CHS-DRG) payment policy is a cornerstone of China’s transition to value-based healthcare. Its successful implementation hinges on the knowledge, attitudes, and practices (KAP) of healthcare professionals, particularly in the large hospitals that are the main arenas for this reform. This study aimed to examine the KAP of healthcare professionals in tertiary and secondary hospitals in Yunnan Province and to analyze the interrelationships between these core constructs.MethodsA cross-sectional survey was conducted from March to May 2023 among 357 healthcare professionals from 30 tertiary and secondary hospitals in Yunnan Province. A self-administered questionnaire was used to collect data on demographics and KAP regarding the CHS-DRG policy. Structural equation modeling (SEM) was employed to test the hypothesized relationships between knowledge, attitudes, and practices, while analysis of variance (ANOVA) was used to explore differences across demographic groups.ResultsThe study found that healthcare professionals possessed moderate knowledge (mean score: 4.01/6) and practice levels, but held generally positive attitudes (mean score: 13.39/18) toward the CHS-DRG policy. The SEM analysis revealed that attitudes (β = 0.462, p < 0.001) had a stronger direct effect on practices than knowledge (β = 0.360, p < 0.001), and that attitudes partially mediated the relationship between knowledge and practice. Furthermore, demographic factors such as age, work experience, and education level were found to have significant, nuanced impacts on specific dimensions of KAP.ConclusionIn the main battleground of China’s DRG reform—tertiary and secondary hospitals—healthcare professionals’ attitudes are a more potent driver of their implementation practices than their formal knowledge. While enhancing policy knowledge is necessary, fostering a positive organizational climate that addresses professional concerns is critical. Implementation strategies should be tailored to the specific needs of different demographic subgroups to effectively translate policy into practice.